Analysis of aggregates and particles in protein pharmaceuticals - Mahler, Hanns-Christian.; Jiskoot, Wim. (Chicester : John Wiley & Sons, 2012)
This book describes how to address the analysis of aggregates and particles in protein pharmaceuticals, provides a comprehensive overview of current methods and integrated approaches used to quantify and characterize aggregates and particles, and discusses regulatory requirements. Analytical methods covered in the book include separation, light scattering, microscopy, and spectroscopy.
III INTEGRATED APPROACHES TO PROTEIN AGGREGATION AND PARTICLES13 Comparison of Methods for Soluble Aggregate Detection and Size Characterization; 14 Protein Purification and Its Relation to Protein Aggregation and Particles; 15 Formulation Development and Its Relation to Protein Aggregation and Particles; Index.
Includes bibliographical references.
Print version record.
Keywords: Pharmaceutical chemistry; Protein drugs -- Analysis; Chemistry Techniques, Analytical -- methods; Pharmaceutical Preparations -- analysis; Proteins -- pharmacokinetics; Pharmacy; Medicine; Electronic books